3D intrinsic shapes of quiescent galaxies in observations and simulations. Issue 4 (23rd May 2022) - Zhang, Junkai; Wuyts, Stijn; Witten, Callum; Avery, Charlotte R; Hao, Lei; Sharma, Raman; Shen, Juntai; Toshikawa, Jun; Villforth, Carolin
ABSTRACT: We study the intrinsic 3D shapes of quiescent galaxies over the last half of cosmic history based on their axial ratio distribution. To this end, we construct a sample of unprecedented size, exploiting multiwavelength u -to- Ks photometry from the deep wide-area surveys KiDS+VIKING paired with high-quality i -band imaging from HSC-SSP. The dependences of the shapes on mass, redshift, photometric bulge prominence and environment are considered. For comparison, the intrinsic shapes of quenched galaxies in the IllustrisTNG simulations are analysed and contrasted with their formation history. We find that over the full 0 < z < 0.9 range, and in both simulations and observations, spheroidal 3D shapes become more abundant at $M_* \gt 10^{11}\, M_{\odot }$, with the effect being most pronounced at lower redshifts. In TNG, the most massive galaxies feature the highest ex situ stellar mass fractions, pointing to violent relaxation via mergers as the mechanism responsible for their 3D shape transformation. Larger differences between observed and simulated shapes are found at low to intermediate masses. At any mass, the most spheroidal quiescent galaxies in TNG feature the highest bulge mass fractions, and, conversely, observed quiescent galaxies with the highest bulge-to-total ratios are found to be intrinsically the roundest. Finally, we detect an environmental influence on galaxy shape, at least at the highest masses, such that at fixed mass and redshift, quiescent galaxies tend to be rounder in denser environments.